An unusual uveitis in Tanzanian children. Issue 6695 (5th August 1989) - Yorston, D.; Foster, A.; Treharne, J.
Abstract : In 1982-7, 254 children with panuveitis were seen at Mvumi Hospital, Tanzania, representing 56% of all cases of uveitis seen. Half were aged under 2. No consistent abnormality accounted for the uveitis and it resolved spontaneously over 6-12 weeks. A trial of prednisolone was performed in 30 children: 18 showed improvement by four weeks compared with 20 of 35 controls given only topical steroids and mydriatics.